2017
DOI: 10.1093/infdis/jix471
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin A Protease Variants Facilitate Intracellular Survival in Epithelial Cells By Nontypeable Haemophilus influenzae That Persist in the Human Respiratory Tract in Chronic Obstructive Pulmonary Disease

Abstract: IgA proteases B1 and B2 cleave LAMP1 and mediate intracellular survival in respiratory epithelial cells. Intracellular persistence of NTHi selects for expression of IgA proteases B1 and B2. The variants of NTHi IgA proteases play distinct roles in pathogenesis of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…This important observation suggests that changes in SSRs, and thus regulation of expression genes by slipped-strand mispairing, are driven by selective pressure in the human airways. This observation is consistent with recent work that shows that passage of NTHi strains through human respiratory epithelial cells selects for expression of IgA proteases that are regulated by slipped-strain mispairing (66).…”
Section: Discussionsupporting
confidence: 93%
“…This important observation suggests that changes in SSRs, and thus regulation of expression genes by slipped-strand mispairing, are driven by selective pressure in the human airways. This observation is consistent with recent work that shows that passage of NTHi strains through human respiratory epithelial cells selects for expression of IgA proteases that are regulated by slipped-strain mispairing (66).…”
Section: Discussionsupporting
confidence: 93%
“…The igaB1 gene has been reported to be more prevalent in COPD exacerbation-causing strains, although the in vivo expression levels did not differ from asymptomatic colonization strains that also carried the gene ( 226 ). However, IgA-protease B1 and B2 have been found to promote the intracellular survival of NTHi in human epithelial cells, providing a secondary function (in addition to hydrolysis of IgA antibodies) that could facilitate NTHi growth in inflamed environments ( 227 ). While a majority of the persistent NTHi strains that dwell in COPD patients continuously express one or more variants of the enzyme, it has recently been found that a phase variation to an OFF-state can occur via slipped-strand mispairing over time ( 228 ).…”
Section: Colonization and Adaptation Of Nthi In The Lower Airways Of mentioning
confidence: 99%
“…It has been suggested that IgA-A and IgA-B proteases have different roles in H. influenzae pathogenesis, and may be variably expressed during different phases of host colonization and invasion [ 13 ]. While IgA-A is implied in tissue colonization and invasion, IgA-B cleaves Lysosomal-associated membrane protein 1 (LAMP-1), which has been suggested to be important for bacterial persistence [ 14 ].…”
Section: Discussionmentioning
confidence: 99%